An investigation on structural and optical properties of Zn1-xMgxS thin films deposited by RF magnetron co-sputtering technique - Bashar M.S.; Yusoff Y.; Abdullah S.F.; Rahaman M.; Chelv P.; Gafur A.; Ahmed F.; Akhtaruzzaman M.; Amin N. (MDPI AG, 2023)
In this paper, Zn1-xMgxS thin films were co-sputtered on glass substrates using ZnS and MgS binary target materials under various applied RF power. The compositional ratio of Zn1-xMgxS films was varied by changing the RF power at an elevated temperature of 200 C. The structural and optical properties were studied in detail. The structural analysis shows that the co-sputtered Zn1-xMgxS thin films have a cubic phase with preferred orientation along the (111) plane. The lattice constant and ionicity suggest the presence of a zincblende structure in Zn1-xMgxS thin films. Zn1-xMgxS thin films have transmittance over 76%. The extrapolation of optical characteristics indicates that direct bandgaps, ranging from 4.39 to 3.25 eV, have been achieved for the grown Zn1-xMgxS films, which are desirable for buffer or window layers of thin film photovoltaics. 2020 by the authors.